Drawing PT-phase envelopes and calculating critical points for multicomponent systems using flash calculations - L. A. Toro (Тонкие химические технологии)
Objectives. This study aims to draw PT-phase envelopes and calculate the critical points for multicomponent systems using flash calculations.Methods. Flash calculations with an equation of state and a mixing rule were used to construct phase envelopes for multicomponent systems. In general, the methodology uses the Soave–RedlichKwong equation of state and Van der Waals mixing rules; and the Peng–Robinson equation of state with Wong–Sandler mixing rules and the non-random two-liquid activity coefficient model.Results. The method was applied to the following mixtures: ethane (1)–butane (2) (four different compositions); ethane (1)–propane (2) (four different compositions); butane (1)–carbon dioxide (2) (three different compositions); C2C3C4C5C6 (one composition); isobutane–methanol–methyl tertbutyl ether–1-butene (one composition); and propylene–water–isopropyl alcohol–diisopropyl ether (one composition).Conclusions. Our results agreed to a large extent with the experimental data available in the literature. For mixtures that contained CO2 , the best results were obtained using the PengRobinson equation of state and the Wong–Sandler mixing rules. Our methodology, based on flash calculations, equations of state, and mixing rules, may be viewed as a shortcut procedure for drawing phase envelopes and estimating critical points of multicomponent systems.